Knowledge and Preventive Action of Pulmonary Tuberculosis Transmission in Household Contacts - Saflin Agustina; Chatarina Umbul Wahjuni (Universitas Airlangga, 2017)
Tuberculosis (TB) is a directly infectious disease caused by Mycobacterium tuberculosis. Knowledge, attitudes, and actions regarding the prevention of pulmonary TB transmission are urgently needed to prevent the transmission of pulmonary TB in the family environment. The purpose of this study was to analyze differences in the behavior of the prevention of pulmonary TB disease transmission in household contacts in the work area of the Public health center (PHC) of Rangkah, Pacar Keling, and Gading City of Surabaya in 2015. This research was observational analytic with a case-control study design. This study used 25 case samples and 25 control samples. Data collection using a questionnaire. The variables studied were preventive measures for pulmonary TB disease transmission, socioeconomic status, gender, knowledge, and attitude. Data analysis used the Chi-square test and Wilcoxon Mann Whitney. The results showed the majority of respondents had low socioeconomic status (72%), were female (58%), had good knowledge (78%), good attitude (72%), and preventive measures for pulmonary TB transmission were good (56%). The results showed that there were differences in sex (p = 0.010), knowledge (p = 0.018) and actions (p = 0,000) prevention of pulmonary TB disease transmission in household contacts, while socioeconomic status (p = 0.533) and attitude (p = 0.212) did not have a significant difference. The conclusion of this study is that there are differences in sex and behavior which includes knowledge and preventive measures for pulmonary TB disease transmission in household contacts.It is recommended the need for cooperation and intervention from health workers through approaches to families and patients in order to prevent transmission of pulmonary TB disease.